The Effect of The Venn strategy on Reading Comprehension and Logical Thinking Among Fifth-Grade Literary Students (Journal of the College of Basic Education, 2024)
The research aims to identify (the effect of the Venn strategy on reading comprehension and logical thinking among fifth grade literary students). The researcher adopted the experimental method with partial control for the two research groups (experimental and control) as a research design, and the researcher randomly chose a research sample consisting of (60) With a reality (30) female students in the experimental group, and (30) female students in the control group. The researcher rewarded the two groups with the following variables: (chronological age calculated in months, the previous year’s grades in the Arabic language subject, the pre-logical reasoning test, and the linguistic ability test, intelligence test, The measurement tool was the same for the two research groups (experimental and control), which was the post-test in reading comprehension and logical thinking, The results showed that the female students who studied the reading subject according to the Venn strategy were superior to the female students who studied the same subject in the usual traditional way.